Vietnam's research and development system in the 1990s: Structural and functional change. Research report - Werner Meske; Dang Duy Thinh (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
Under the ca. 15 years of doi moi (renovation) policy, Vietnam's development has been taking place in the two different but overlapping contexts of transformation and swift economic development. These contexts correspond to two different scenarios for the country's future: One scenario of transformation is the Eastern European pattern; the other is the Tiger Scenario, with increasing industrialisation and rapid economic growth. The research and development (R&D) potential created during the period of planned economy could assume a key role in these processes. In the 1990s the R&D system was restructured, with the aim of solving the financial problems that had arisen during transformation, while at the same time seeking to better achieve a functional integration of R&D into innovation processes in the economy. A joint research project carried out by the 'Working Group Transformation of Science Systems (WZB) and the NISTPASS, Hanoi conducted macrostructural research and in-depth case studies in selected industrial sectors and R&D institutions to clarify how this is taking place, which organisational forms are created by it, and how the new structures affect the functions of R&D. This report presents the results of this research. The impact of doi moi policy in the area of S&T must be described as ambiguous: There is an incongruity between successful structural changes and their functional effects, in particular regarding increased innovation activities - which have so far not or only partially been achieved. Some serious problems in the science system, in industrial enterprises as targets of innovations and in infrastructural prerequisites for innovation diminish Vietnam's current and future potential to utilise R&D for economic growth and social welfare. – – Die Entwicklung Vietnams verläuft seit etwa 15 Jahren unter der doi moi (Erneuerungs-) Politik in zwei verschiedenen, einander überlagernden Kontexten der Transformation und der raschen Wirtschaftsentwicklung. Diesen beiden Kontexten entsprechen unterschiedliche Szenarien für die künftige Entwicklung: Ein Transformationsszenario nach osteuropäischem Muster und ein ,Tigerszenario' mit zunehmender Industrialisierung und einem raschen Wirtschaftswachstum. Dem in der planwirtschaftlichen Periode geschaffenen Forschungs- und Entwicklungs- (FuE) Potential könnte eine Schlüsselrolle in der künftigen Entwicklung zukommen. In den 90er Jahren erfolgte eine Umstrukturierung des FuE-Systems, die das Ziel verfolgt, die im Zusammenhang mit der Transformation entstandenen Finanzierungsprobleme zu lösen und gleichzeitig seine funktionelle Einbindung in das Innovationsgeschehen in der Wirtschaft zu erreichen. Wie dies geschieht, welche Organisationsformen dabei entstehen und wie die neuen Strukturen die Funktionen der FuE beeinflussen, wurde durch ein gemeinsames Projekt der Arbeitsgruppe Wissenschaftstransformation des WZB und des NISTPASS untersucht. In diesem Heft werden Ergebnisse dieses Projekts vorgestellt. Die Auswirkungen der doi moi Politik auf Wissenschaft und Technik müssen als zwiespältig charakterisiert werden: Es gibt ein Missverhältnis zwischen erfolgreichen Strukturveränderungen und deren funktionellen Auswirkungen, insbesondere hinsichtlich verstärkter Innovationsaktivitäten, die bisher nicht oder nur teilweise erreicht worden sind. Einige ernsthafte Probleme innerhalb der Wissenschaft, in den Industriebetrieben, die Ziel der Innovationen sind, und in der relevanten Infrastruktur vermindern Vietnams aktuelle wie künftige Möglichkeiten, FuE für Wirtschaftswachstum und Wohlstand nutzbar zu machen.
Keywords: 300; Wissenschaft; Forschung; Industrielle Forschung; Innovation; Systemtransformation; Vietnam